(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
Based on the experimental studies, carried out in this work, and the scientific and practical justification of their results, it can be shown that varying of the synthesis conditions (such as concentration of iron and gadolinium salts, the nature of the precipitant , pH, temperature) results in the formation of mixed ensembles - aggregates consisting of nanoparticles of iron and gadolinium oxides and hydroxides in the structure stabilizer – humic acids. It has been shown that when using the chemical coprecipitation method (as opposed to the aging method) in a narrow pH range, the formation of an ensemble of particles consisting mainly of iron and gadolinium oxides is observed. Analysis of the magnetic characteristics of the synthesized humic composite materials showed that the total number of spectral overlaps is proportional to the number of reflections and is characterized by a repeatability factor. This factor value for these samples of humic composites describes their minimum amount, and therefore corresponds to crystals with an average cell.